Frontispiece: Peptide‐Based Molecular Hydrogels as Supramolecular Protein Mimics. Issue 5 (23rd January 2017) - Singh, Nishant; Kumar, Mohit; Miravet, Juan F.; Ulijn, Rein V.; Escuder, Beatriu
Abstract : Peptidic hydrogelators In their Minireview onpage 981 ff., J. F. Miravet, R. V. Ulijn, B. Escuder et al. discuss recent advances in the design, synthesis, and application of low molecular‐weight peptidic hydrogelators. Prevalent types of these structures include N ‐capped amino acid residues, bolamphiphilic peptides, and amphipathic peptides, whereas hydrophobic effects, the Hofmeister effect, and tunable ionization influence their aggregation properties. The self‐assembly of bio‐inspired building blocks enables comparison with proteins and their complex functionalities, providing preliminary insights into complex biological functions and also enabling their application in a wide range of fields.